Dietary specialization and climatic-linked variations in extant populations of Ethiopian wolves - Marino, J; Mitchell, R; Johnson, P (2010)
Understanding of the biology of rarity is central to the conservation of some endangered species. Rare taxa are often reported to be specialized, but they are usually poorly studied. The Ethiopian wolf (Canis simensis) is endemic to the Ethiopian highlands and in two major populations, Bale and Arsi in the southern range of the species, it preys almost exclusively upon diurnal rodents all year round, mainly molerats Tachyoryctes macrocephalus and common molerats T. splendens, respectively. Where these large rodents are absent or rare, wolves are expected to rely more heavily on nocturnal rats or livestock. Prey remains in 161 scats from five newly studied populations confirmed that wolves are indeed specialist rodent hunters elsewhere, and that their narrow diets are dominated by diurnal Murinae rats (60-83% of prey occurrences). Swamp rats Otomys typus were the main prey, followed by grass rats Arvicanthis abyssinicus. Common molerats, Lophuromys rats and nocturnal Stenocephalemys spp. constituted the variable portion of the diets, and their proportional contributions varied across populations in relation to elevation and latitude. Towards the north, where the climate is drier and human populations more dense, wolves predate more frequently on rat-sized prey, including nocturnal species, with implications for the survival of small populations in the Northern Highlands. © 2009 The Authors. Journal compilation © 2009 Blackwell Publishing Ltd.